La opacidad de los acuerdos generales de bienes y servicios en España Opacity of general agreements on goods and services in Spain - Román Andrés Umaña Peña; Carlos Álvarez-Dardet Díaz; Carmen Vives Cases (Elsevier, 2006)
Objetivo: Explorar la intensidad del debate parlamentario sobre el Acuerdo General de Comercio de Servicios (AGCS) asumido por España ante la Organización Mundial del Comercio (OMC), y compararla con la del Acuerdo General de Bienes (GATT). Métodos: Búsqueda sistemática y análisis del contenido de todas las iniciativas parlamentarias sobre AGCS y GATT realizadas entre 1979 y 2004 en el Congreso de los Diputados y el Senado. Se calculó la frecuencia y porcentaje de iniciativas parlamentarias de ambos temas, resultado de su tramitación y tipo de iniciativa. Resultados: Se presentaron 185 iniciativas parlamentarias sobre los acuerdos multilaterales de bienes y servicios, de las que 120 se referían al GATT, 8 al AGCS y 57 a ambos acuerdos. La mayoría de las iniciativas no fueron discutidas (GATT, 71%; GATS, 55,4%) o estuvieron sujetas a un debate político en el que apenas se dieron intervenciones por parte de los grupos parlamentarios. Conclusiones: A pesar de las implicaciones del acuerdo multilateral de servicios para la política sanitaria española, éste se ha asumido con escaso debate parlamentario previo, incluso menos que en el caso de su homólogo sobre bienes. Se requiere en este tema una intensificación de la función de control al gobierno. Objective: To explore the intensity of the debate in the Spanish Parliament on the General Agreement on Trade in Services (GATS) developed by Spain and the World Trade Organization, and to compare it with the debate on the General Agreement on Tariffs and Trade (GATT). Methods: A systematic search and content analysis were performed of all parliamentary initiatives on GATS and GATT undertaken from 1979 to 2004 in the Spanish Parliament and Senate. The frequency and percentages of initiatives on both issues were calculated, and the final result and kinds of initiative were analyzed. Results: A total of 185 initiatives were presented in the Spanish Parliament on these agreements, of which 120 were on GATT, 8 were on GATS and 57 were on both agreements. Most of these initiatives were not discussed in parliament (GATT, 71%; GATS, 55.4%) or were the subject of political debate with low participation among parliamentary groups. Conclusions: Despite the implications of the GATS for Spanish health policy, the agreement was developed with little prior political debate, which was even less intense than that on GATT. The parliamentary function of controlling the government should be reaffirmed in Spain.